Cloning, overproduction, and purification of the B2 subunit of ribonucleoside-diphosphate reductase. - Salowe, S P (1986)
The nrdB gene, which encodes the B2 subunit of Escherichia coli ribonucleotide reductase (EC 1.17.4.1), was cloned into multicopy plasmid pSPS2. This vector, which contains the pL promoter of bacteriophage lambda and the tetracycline resistance gene of pBR322, was transformed into a lysogenic host with a thermolabile repressor. In the newly constructed strain, subunit B2 constituted approximately 25% of the soluble protein after heat induction, an overproduction of several hundredfold relative to the wild-type strain. Purification to homogeneity of the overproduced protein was accomplished by using DEAE and quaternary aminoethyl ion-exchange resins.